(untitled) (Construction Economics and Building, 2013)
Power transmission facilities in the U.S. are undergoing a transformation due to the increased use of distributed generation sources such as wind and solar power. The current power grid system is also antiquated and in need of substantial retrofits to make it more efficient and reliable. The new energy transmission system being designed and built to optimize power delivery is known as “Smart Grid”. The increased activity in the construction of power transmission facilities and installation of new technologies into the current power system raises potential safety concerns. Existing construction management curriculum may include general information about safety training, but does not typically include information about this specialized sector. The objective of this study was to work with industry to identify key safety topics appropriate for inclusion in an introductory industrial construction course. Results of interviews with industry identified numerous hazards that are not typically covered in typical construction curricula. A joint undergraduate and graduate course in industrial construction was created to address these and additional concepts. A survey of the students was performed to determine the effectiveness of the course and also to determine their thoughts about the smart grid technologies and safety training. Information on electrical system hazards is presented along with results of the student surveys.